Kajian pelaksanaan sistem pengurusan kualiti berteraskan syariah MS 1900 DI Darul Quran, JAKIM / Muhammad Firdaus Zakaria - Muhammad Firdaus , Zakaria (2018)
Shari‘ah-based Quality Management System, MS 1900 is the world's first Islamic quality management system introduced by the Malaysian government in 2005. The establishment of the MS 1900 was aimed at empowering the organizational governance through the application of Islamic values into the practice of quality management system. The literature shows that although the MS 1900 study was conducted by previous researchers, studies on the implementation of MS 1900 at Islamic higher education institutions have never been done. Hence, this empirical study is focused on the implementation of MS 1900 Shari‘ah-based Quality Management System at Darul Quran JAKIM. The objective of this study is to explore four key aspects of the implementation of MS 1900 in Darul Quran JAKIM which include the steps that have been taken, the influencing factors, the challenges faced and the benefits gained. Qualitative approaches (case studies) were used through triangulation data collection which are interviews, documentation and observation. The data were processed using thematic analysis to establish codes and themes for research issues. The findings show that nine steps have been taken, six influencing factors, five challenges and also five benefits, have been identified through the implementation of MS 1900 at Darul Quran JAKIM. The implication of this study proves that the implementation of MS 1900 is capable of enhancing management competencies in the organization, especially in Islamic-oriented higher education institution, that includes several aspects which are management system, infrastructure, syllabus and the practice of Islamic values which in turn leads to the development of national human capital. The results of this study have contributed to the development of knowledge about the implementation of MS 1900 in the environment of Islamic learning institutions. The results of this study also can be used by managers in the public or corporate sectors in their quest to effectively implement MS 1900.